Ordinance No. 51: An Ordinance to Establish a Criminal Code, THE GLOBE JOURNAL, Jun. 5, 1880, at 2, § 11 - (:unkn) unknown (My University, 1880)
§ 11: Whoever shall carry a weapon, or weapons, concealed on or about his person, such as a pistol, bowie knife, dirk, or any other dangerous weapon, shall be fined not exceeding one hundred dollars, or imprisoned in jail not more than thirty days
Keywords: CARRY - CONCEALED